Pendugaan Daya Simpan Manisan Tomat Kering dengan Metode ASLT (Accelerated Shelf-Life Testing) Model Arrhenius - Djarkasi, G. S. Suhartati; Sumual, Maria F.; Lalujan, Lana E. (Fakultas Pertanian, Universitas Sam Ratulangi, 2017)
This study aims to make dried tomato sweets and to estimate their shelf life using the Arrhenius model of ASLT (Accelerated Shelf-life Testing). The ASLT method with the Arrhenius Model is a=technique for predicting the shelf-life of food products that is sensitive to temperature changes. The tests were carried out at temperatures of 30â°C, 40â°C, and 50â°C, the products stored for 25 days to see the quality changes through sensory evaluation, including color, taste, texture, and aroma of dried tomato sweets. It was selected by the Arrhenius model that color parameters was the critical parameter to determine the shelf life of dried tomato sweets. The largest R2 value was used to determine the shelf-life of the product, i.e. the preference test of taste which showed the reaction at 0 (zero) order by the equation y = -2045,8x + 3,5196 with R2 = 0,9886. The shelf life of dried tomato sweets is 3 months 11 days.Keywords: Shelf-life, dried sweetened tomato, ASLT model.